2010
DOI: 10.1001/archfacial.2010.33
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Techniques Used to Support the Nasal Tip and Their Long-term Effects on Tip Position

Abstract: Many factors influence the maintenance of tip position in patients who have undergone rhinoplasty. One should consider using a stabilization technique to help resist displacement of the nasal tip. Clinical and operative findings, as well as secondary effects, are used to help determine which technique should be used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 6 publications
1
34
1
Order By: Relevance
“…In these cases, the implant serves as a buttress to support the mass of the nasal tip. 18 The skin and mucosa covering the implant in this region are thin, and their vascularity may be compromised, especially in revision cases. Also, this region of the nose is mobile and subject to repetitive trauma.…”
Section: Commentmentioning
confidence: 99%
“…In these cases, the implant serves as a buttress to support the mass of the nasal tip. 18 The skin and mucosa covering the implant in this region are thin, and their vascularity may be compromised, especially in revision cases. Also, this region of the nose is mobile and subject to repetitive trauma.…”
Section: Commentmentioning
confidence: 99%
“…Some work in this area has been performed. Beaty et al, 10 Dobratz et al, 12 and Wilson et al 11 were able to measure this reaction force to displacement using novel devices. Beaty et al 10 found that 35.54, 61.24, and 89.40 g were required to displace the nasal tip 1, 2, and 3 mm, respectively, along the vector of the columella.…”
Section: Discussionmentioning
confidence: 99%
“…Beaty et al 10 found that 35.54, 61.24, and 89.40 g were required to displace the nasal tip 1, 2, and 3 mm, respectively, along the vector of the columella. Dobratz et al 12 found that 25 and 50 g were needed to depress the nasal tip approximately 1 and 2 mm, respectively. Wilson et al 11 found that a mean of 1.0 to 3.4 N were needed to compress the nasal tip of a fresh-thawed cadaver from 0.5 to 2.5 mm, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations